Origin of volatile organic compound emissions from subarctic tundra under global warming - Ghirardo, Andrea; Lindstein, Frida; Koch, Kerstin; Buegger, Franz; Schloter, Michael; Albert, Andreas; Michelsen, Anders; Winkler, J. Barbro; Schnitzler, Jörg‐Peter; Rinnan, Riikka (Global change biology, 2020)
Warming occurs in the Arctic twice as fast as the global average, which in turn leads to a large enhancement in terpenoid emissions from vegetation. Volatile terpenoids are the main class of biogenic volatile organic compounds (VOCs) that play crucial roles in atmospheric chemistry and climate. However, the biochemical mechanisms behind the temperature‐dependent increase in VOC emissions from subarctic ecosystems are largely unexplored. Using 13CO2‐labeling, we studied the origin of VOCs and the carbon (C) allocation under global warming in the soil–plant–atmosphere system of contrasting subarctic heath tundra vegetation communities characterized by dwarf shrubs of the genera Salix or Betula. The projected temperature rise of the subarctic summer by 5°C was realistically simulated in sophisticated climate chambers. VOC emissions strongly depended on the plant species composition of the heath tundra. Warming caused increased VOC emissions and significant changes in the pattern of volatiles toward more reactive hydrocarbons. The 13C was incorporated to varying degrees in different monoterpene and sesquiterpene isomers. We found that de novo monoterpene biosynthesis contributed to 40%–44% (Salix) and 60%–68% (Betula) of total monoterpene emissions under the current climate, and that warming increased the contribution to 50%–58% (Salix) and 87%–95% (Betula). Analyses of above‐ and belowground 12/13C showed shifts of C allocation in the plant–soil systems and negative effects of warming on C sequestration by lowering net ecosystem exchange of CO2 and increasing C loss as VOCs. This comprehensive analysis provides the scientific basis for mechanistically understanding the processes controlling terpenoid emissions, required for modeling VOC emissions from terrestrial ecosystems and predicting the future chemistry of the arctic atmosphere. By changing the chemical composition and loads of VOCs into the atmosphere, the current data indicate that global warming in the Arctic may have implications for regional and global climate and for the delicate tundra ecosystems. We studied the origin of biogenic volatile organic compounds (VOCs) and carbon (C) allocation under global warming in subarctic heath tundra ecosystem using isotope labeling of 13CO2. Our results show the importance of de novo monoterpene biosynthesis and the impact of warming in vegetation communities characterized by Salix spp. (willows) or Betula spp. (birch). Warming increased overall VOC emissions and altered the composition of the volatile blend toward more reactive compounds. Analyses of above‐ and belowground 12/13C suggest shifts of C allocation and negative effects of warming on C sequestration in these delicate tundra ecosystems.